Polyploid Superficial Cells that Maintain the Urothelial Barrier Are Produced via Incomplete Cytokinesis and Endoreplication - Wang, Jia; Batourina, Ekatherina; Schneider, Kerry; Souza, Spenser; Swayne, Theresa; Liu, Chang; George, Christopher D.; Tate, Tiffany; Dan, Hanbin; Wiessner, Gregory; Zhuravlev, Yelena; Canman, Julie C.; et al. (Cell reports (Cambridge), 2018)
The urothelium is an epithelia barrier lined by a luminal layer of binucleated, octoploid, superficial cells. Superficial cells are critical for production and transport of uroplakins, a family of proteins that assemble into a waterproof crystalline plaque that helps protect against infection and toxic substances. Adult urothelium is nearly quiescent, but rapidly regenerates in response to injury. Yet the mechanism by which binucleated, polyploid, superficial cells are produced remains unclear. Here, we show that superficial cells are likely to be derived from a population of binucleated intermediate cells, which are produced from mononucleated intermediate cells via incomplete cytokinesis. We show that binucleated intermediate and superficial cells increase DNA content via endoreplication, passing through S phase without entering mitosis. The urothelium can be permanently damaged by repetitive or chronic injury or disease. Identification of the mechanism by which superficial cells are produced may be important for developing strategies for urothelial repair. [Display omitted] •Binucleated S-cells are critical for maintaining the urothelial barrier•S-cells derive from tetraploid I-cells that form via incomplete cytokinesis•Binucleated I- and S-cells increase ploidy via endoreplication•Polyploidy may enable the urothelium to efficiently adjust to environmental changes Binucleated superficial cells are critical for urothelial barrier function. Wang et al. show that they derive from binucleated intermediate cells that form via incomplete cytokinesis. Both superficial and intermediate cells increase ploidy via endoreplication, a feature likely to be important for repair and response to environmental changes.